Role of KIM-1 in early diagnosis of contrast-induced nephropathy following invasive cardiac procedure: A systematic review - Mantasha Shuaib; Md Masoom; Mohd Ashif Khan (Elsevier, 2024)
This systematic review aims to provide a comprehensive analysis of the diagnostic efficacy of KIM-1 in CI-AKI. We evaluated its potential as a robust biomarker for the early identification and prediction of AKI progression. Methodology: To assess KIM-1 as a biomarker for CI-AKI, relevant databases were searched. Inclusion criteria comprised studies measuring KIM-1 levels in patients undergoing cardiac procedures with contrast media and data were extracted. Methodological quality and bias were evaluated using Quadas-2 tool. Conclusion: KIM-1 shows promise as a biomarker for renal injury. Its upregulation, correlation with injury severity, and involvement in tissue repair support its clinical relevance. Prospero registration number: CRD42023431419.